Allelic association and functional studies of promoter polymorphism in the leukotriene C4 synthase gene (LTC4S) in asthma. Issue 5 (1st May 2003) - Sayers, I; Barton, S; Rorke, S; Beghé, B; Hayward, B; Van Eerdewegh, P; Keith, T; Clough, J B; Ye, S; Holloway, J W; Sampson, A P; Holgate, S T
Abstract : Background: LTC4 synthase is essential for the production of cysteinyl leukotrienes (Cys-LT), critical mediators in asthma. We have identified a novel promoter polymorphism at position −1072 (G/A) and a −444 (A/C) polymorphism has previously been reported. The role of these polymorphisms in the genetic susceptibility to asthma was examined. Methods: To test for genetic association with asthma phenotypes, 341 white families (two asthmatic siblings) and 184 non-asthmatic control subjects were genotyped. Genetic association was assessed using case control and transmission disequilibrium test (TDT) analyses. LTC4S promoter luciferase constructs and transiently transfected human HeLa and KU812F cells were generated to determine the functional role of these polymorphisms on basal transcription. Results: No associations were observed in case control analyses (–1072 A, q=0.09; −444 C, q=0.29); the TDT identified a borderline association between the −444 C allele and bronchial responsiveness to methacholine (p=0.065). Asthmatic children with the −444 C allele had a lower mean basal forced expiratory volume in 1 second (97.4 v 92.7% predicted, p=0.005). LTC4S promoter luciferase analyses provided no evidence for a functional role of either polymorphism in determining basal transcription. Conclusion: This study does not support a role for these polymorphisms in genetic susceptibility to asthma but provides evidence to suggest a role in determining lung function parameters.